Fractional-Order Williamson Fluid Flow with Slip and Cross-Diffusion Over a Variable-Thickness Sheet - Shah, Ravi S.; Raj, Heenaben A.; Trivedi, Gargi J. (Communications in Mathematics and Applications, 2025)
This study investigates heat and mass transfer in non-Newtonian Williamson fluid flow over a variable-thickness stretching sheet, incorporating Caputo fractional derivatives, velocity slip conditions, and Soret and Dufour effects. A fractional-order model captures memory effects, enhancing the representation of shear-thinning behavior and cross-diffusion phenomena. Governing equations are solved numerically using a hybrid Crank-Nicolson and spectral method, with stability and convergence rigorously analyzed. Results reveal that increasing the fractional order \((α)\) from 0.1 to 0.9 yields a 300% increase in heat transfer rate (from 250 W/m\(^2\) to 1000 W/m\(^2\)) and a 53% reduction in thermal boundary layer thickness (from 0.015 m to 0.007 m). Slip conditions further reduce boundary layer thickness by 16%, while magnetic field and cross-diffusion effects amplify transfer rates by 43%. The model offers 20-30% improved accuracy over traditional approaches, with applications in polymer extrusion and biomedical microfluidics. Future work will explore variable material properties and multi-phase flows.